A study of the association of thyroid-stimulating hormone levels with microvascular complications in type 2 diabetes mellitus patients at a tertiary care center - Somnath B; Pooja Shashidharan; Manish Pangi (Asian Journal of Medical Sciences, 2025)
Background: Diabetes mellitus (DM) and hypothyroidism are two of the most common metabolic diseases worldwide. The prevalence of both conditions is drastically on the rise and if untreated is associated with long-term complications. Several studies have established the association between hypothyroidism and microvascular complications of diabetes. However, with the ever increasing diagnosis of sub-clinical hypothyroidism among diabetics, its association with the microvascular complications of DM needs to be studied. Aims and Objectives: The aims of this study were to study the association between thyroid-stimulating hormone (TSH) levels and microvascular complications of type 2 DM (T2 DM). DM is a metabolic disease which affects various organs of the body. The prevalence of T2 DM is on the rise much more rapidly, which is due to increasing obesity and reduced activity levels. Undiagnosed thyroid dysfunction may affect metabolic control and enhance cardiovascular and other chronic complication in diabetic patients. Materials and Methods: A total of 50 T2 DM patients were enrolled in this cross-sectional study. Subjects were evaluated for thyroid function, microvascular complications such as peripheral neuropathy, diabetic retinopathy, and diabetic kidney disease. TSH was divided into three levels: 0.27–2.49 mU/L, 2.5–4.2 mU/L, and >4.2 mU/L. The association between TSH levels and microvascular complications of T2 DM was studied. Results: Our study found a statistically positive association elevated TSH and microalbuminuria, macroalbuminuria, low GFR, and impaired vibration sense. Our study found no association between elevated TSH and retinopathy. Conclusion: It is ideal to screen all patients with T2 DM for thyroid dysfunction as elevated TSH levels in these patients can be an indicator of underlying microvascular complications.